Pendidikan Akhlak Menurut Imam Al-Ghazali - Hanifa Nur Laili; Ainur Rofiq Sofa (Lembaga Pengembangan Kinerja Dosen, 2025)
The current condition of education shows a lack of attention to morals, teachers only transfer knowledge and students only receive it, there is no concern about morals, morals towards teachers and fellow morals, morals towards teachers and fellow students. Based on the background of the problem above, the following problems can be formulated problem as follows: How is moral education according to Imam Al-Ghazali? The purpose of this research is to find out how the concept of moral education according to Imam al-Ghazali. According to Imam al-Ghazali. The data collected in this research analyzed with descriptive analytical method. Based on the analysis, it can be Based on the analysis, it can be concluded that Akhlak according to Al-Ghazali is something that is settled in life and appears in actions easily without the need to think about it. life and appears in action easily without needing to think about it first. first. Morals are not deeds, powers, and knowledge. Akhlak is “Haal” or condition of the soul and inner form.